Place in the science fiction novel (Ajwan) by Noura Al Noman as a model: critical analysis - Alteneiji, Moza; Darabseh, Mahmoud (Al-Adab Journal, 2024)
Science fiction literature in the developed world receives great attention in critical literary circles. It is not possible to search for science fiction novels in the Emirates without coming up with the name of the writer Noura Ahmed Al Noman, who is considered the first writer and novelist specializing in the field of science fiction. Through this research, we shed light on the first Emirati novelist to write a science fiction novel in her novel (Ajwan). Science fiction is the ideal means of linking literary culture and scientific culture. It is a type of fiction that takes the reality of scientific and technological progress on society and individuals as its primary subject. Critics and researchers paid attention to place because of its importance as an authentic element and a basic component that cannot be overlooked or ignored in studying the text, as characters move in a spatial space, and events must have a place in which they occur or take place. Each element of the novel has its own importance.